The fingerprints of intra-continental deformation in central Europe as evisaged by the synergic use of predicting modelling and geodetic data - A.M. Marotta (OGS, 2005)
The large scale crustal deformation geodetically observed in Europe is the result of a complex interplay of different geodynamic forces, such as the Africa-Eurasia plates' convergence, the mid-Atlantic spreading and the post-glacial rebound. Each force has a different impact on the deformation in Europe, with tectonic forces playing the major role in the southernmost part of continental Europe, between the Alpine front and the southern border of Fennoscandia, while the post-glacial rebound mainly affects the deformation at high latitudes, north of Potsdam. The lateral rheological heterogeneities also have a crucial role in stiffening the propagation of tectonic deformation throughout northern Europe. When Global Positioning System data are used to constrain predictive geophysical modelling, they reveal their crucial role in distinguishing different geodynamic processes responsible for the observed deformation. A comparison between predicted tectonic deformation and geodetic data demonstrates, in fact, that tectonic forces and post-glacial rebound must be simultaneously taken into account for a correct interpretation of the deformation in northern and central Europe measured by geodetic techniques.